Importance of blood pressure lowering in patients with direct oral anticoagulant-associated intracerebral haemorrhage in the acute phase and for secondary prevention - Parry‐Jones, Adrian R.; Moullaali, Tom J; Sandset, Else C; Qureshi, Adnan I; Anderson, Craig S; Steiner, Thorsten (European stroke journal, 2025)
Purpose: Intracerebral haemorrhage (ICH) is an important complication of direct oral anticoagulation (DOAC) therapy, where risks and prognosis are potentially modified by effective blood pressure (BP) control, both in the acute phase and for secondary prevention. Herein, we review BP management in the context of general anticoagulation associated ICH and specifically in DOAC-ICH, considering current evidence and highlighting outstanding questions. - Method: Narrative review. - Findings: Pooled analyses of major trials of BP lowering in acute ICH patients without anticoagulants demonstrate a reduction in the risk of haematoma expansion. As anticoagulant-associated ICH patients tend to be older, have more co-morbidities, and larger haematomas at baseline with a greater risk of expansion, the risks and benefits of intensive BP lowering treatment might both be higher. Small observational studies of DOAC-ICH patients suggest that lower achieved BP is associated with less expansion, lower mortality, and better functional outcomes. Care bundles including both anticoagulant reversal and intensive BP lowering might reduce the risk of death and disability in DOAC-ICH. Optimal control of BP in survivors of ICH reduces the risk of both ischaemic and haemorrhagic stroke but whether this modulates the risks and benefits of restarting a DOAC is unknown. - Discussion: Limited evidence suggests that BP should be well managed in DOAC-ICH patients, in the same way as ICH patients not on anticoagulants, both in the hyperacute phase and for secondary prevention. Hypothetical differences in the effects of BP lowering treatment in DOAC-ICH need to be tested in clinical trials.
Gesehen am 05.11.2025